Salt-Enhanced Reproductive Development of Suaeda salsa L. Coincided With Ion Transporter Gene Upregulation in Flowers and Increased Pollen K+ Content - Guo, Jianrong; Dong, Xinxiu; Han, Guoliang; Wang, Baoshan (Frontiers in Plant Science, 2019)
Halophytes are adapted to saline environments and demonstrate optimal reproductive growth under high salinity. To gain insight into the salt tolerance mechanism and effects of salinity in the halophyte Suaeda salsa, the number of flowers and seeds, seed size, anther development, ion content, and flower transcript profiles, as well as the relative expression levels of genes involved in ion transport, were analyzed in S. salsa plants treated with 0 or 200 mM NaCl. The seed size, flower number, seed number per leaf axil, and anther fertility were all significantly increased by 200 mM NaCl treatment. The Na+ and Cl− contents in the leaves, stems, and pollen of NaCl-treated plants were all markedly higher, and the K+ content in the leaves and stems was significantly lower, than those in untreated control plants. By contrast, the K+ content in pollen grains did not decrease, but rather increased, upon NaCl treatment. Genes related to Na+, K+ and, Cl− transport, such as SOS1, KEA, AKT1, NHX1, and CHX, showed increased expression in the flowers of NaCl-treated plants. These results suggest that ionic homeostasis in reproductive organs, especially in pollen grains under salt-treated conditions, involves increased expression of ion transport-related genes.